Struktur Perilaku Dan Kinerja Pasar Komoditi Karet Di Desa Manggala Kabupaten Melawi - Yustanto, Erik; Maswadi, Maswadi; Suharyani, Anita (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
This study aims to identify marketing channels, find out the structure, behavior and performance of the rubber market in Manggala Village, Melawi Regency.The market structure approach uses market share (market share), concentration ratio, and market entry barriers. The approach to market behavior using qualitative descriptive analysis explains with regard to the pricing system, and cooperation between marketing agencies.while the market performance approach uses marketing margin analysis. The respondents to the study were 67 rubber farmers and 13 marketing agencies involved in distributing rubber from producers to factories. The results showed that the structure of the rubber market in Manggala Village, Melawi Regency, led to an oligopoly. Based on the results of a descriptive analysis of market behavior, results were obtained in the process of pricing at the farmer level that farmers are not as determinants of prices but rather prices are determined by collecting traders and wholesalers. At the level of farmers and marketing institutions, there are as many as 21 people who cooperate with collecting merchants who have grocery stores, namely in the form of basic food debt,and paid when farmers sell their rubber production At the level of marketing institutions with marketing agencies, the cooperation carried out is with the provision of business capital to buy rubber from farmers and in the form of transportation of rubber picks to the place of collecting traders. The performance of the rubber market has not been efficient because the margins and profits of marketing institutions are uneven and farmers are the most disadvantaged because farmers are only price takers.